A New Surfactant Flooding Model for Low Permeability Reservoirs - Li, Yongwei; Yin, Lizhong (Scientific Research, 2013)
Surfactant as a successful Enhanced Oil Recovery (EOR) agent has been widely used in many mature reservoirs. This research focuses on the description of surfactant solution at low permeability condition. A new three-dimensional, two phase, three-component surfactant simulator is presented. The simulator is based on the non-Darcy flow characteristics of surfactant flooding in the low permeability formations. The change of threshold pressure and influences of surfactant on convection, diffusion, adsorption, and retention, are all considered. A new equation for the calculation of surfactant adsorption is employed, which can significantly promote the matching degree between the mathematical model and field practice. The design of this new simulator is to help the decision-making in the reservoir engineering analysis of surfactant EOR projects, to face the challenge of the design of injection schemes, to assist the surfactant screening, to screen and assess laboratory and field data and their effect on the performance predictions, and to find the optimal methods of field development.
Keywords: Surfactant Flooding; Simulation; Threshold Pressure; Pilot Test